Answer to Question #218210 in Differential Equations for TORRES

Question #218210
  1. y(3x^3-x+y)dx+x^2(1-x^2)dy=0
  2. y(2x+y^2)dx+x(y^2-x)dy=0
1
Expert's answer
2021-07-20T17:45:08-0400

Answer:-

1.


"y(3x^3-x+y)dx+x^2(1-x^2)dy=0"

This is the first order nonlinear ordinary differential equation.

Divide on "x^2(1-x^2)dx."



"y'=\\frac{3x^3y-xy+y^2}{x^2(x^2-1)},""y'=\\frac{y^2}{x^2(x-1)(x+1)}+\\frac{3xy}{(x-1)(x+1)}-\\frac{y}{x(x-1)(x+1)},""y'-\\frac{3x^2-1}{x^3-x}y=\\frac{y^2}{x^4-x^2}."

We have Bernuli's equation for n=2.

Divide by "y^2."



"\\frac{y'}{y^2}-\\frac{3x^2-1}{(x^3-x)y}=\\frac{1}{x^4-x^2}."

Replacement "u=\\frac{1}{y}," then "u'=-\\frac{y'}{y^2}, y'=-u'y^2."



"-\\frac{u(3x^2-1)}{x^3-x}-u'=\\frac{1}{x^4-x^2},""u'+(\\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)})u=-\\frac{1}{x^4-x^2}"

This is the first order linear equation.

Let be "P(x)=\\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)}."

"\\int P(x)dx=\\int \\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)}dx=\\ln (x^3-x)+C,"

where C is some constant.

Solve


"u'+P(x)u=0,""\\frac{du}{u}=-P(x)dx,""\\int\\frac{du}{u}=-\\int P(x)dx,""\\ln u =-\\ln (x^3-x)+C,""u=\\frac{C}{x^3-x}."

The solution of "u'+(\\frac{3x}{(x-1)(x+1)}-\\frac{1}{x(x-1)(x+1)})u=-\\frac{1}{x^4-x^2}" find by the method of variation constant in the form "u=\\frac{C(x)}{x^3-x}."



"C(x)=\\int(-\\frac{x^3-x}{x^4-x^2})dx=-\\ln x+C."

Thus "u=\\frac{-\\ln x+C}{x^3-x}."

From here "y=\\frac{x-x^3}{\\ln x+C}."

Answer. "y=\\frac{x-x^3}{\\ln x+C}."

2.



"x(y^2-x)dy=y(y^2+2x)dx=0."

This is the first order nonlinear ordinary differential equation.

Replacement "y=\\sqrt{z}," then "dy=\\frac{dz}{2\\sqrt{z}}." We will have



"(\\frac{c\\sqrt{z}}{2}-\\frac{x^3}{2\\sqrt z})dz=(-z^{\\frac{3}{2}}-2x\\sqrt z)dx."

Replacement "u=\\frac{z}{x}," then

"x=ux, dz=udx+xdu."

We will have



"(\\frac{\\sqrt {u}}{2}-\\frac{1}{2\\sqrt u}x^{3\/2}(udx+xdu)=(-u^{3\/2}-2\\sqrt u)x^{3\/2}dx,""(\\frac{\\sqrt {u}x^{5\/2}}{2}-\\frac{x^{5\/2}}{2\\sqrt u})du=(-\\frac{3u^{3\/2}x^{3\/2}}{2}-\\frac{3\\sqrt u u^{3\/2}}{2})dx."

Divide by "x^{5\/2}" and "-\\frac{3u^{3\/2}x^{3\/2}}{2}-\\frac{3\\sqrt u u^{3\/2}}{2}."

We will have



"(\\frac{1}{3u(u+1)}-\\frac{1}{3(u+1)})du=\\frac{dx}{x}."

"\\int(\\frac{1}{3u(u+1)}-\\frac{1}{3(u+1)})du=\\int\\frac{dx}{x}."

"\\frac{\\ln u}{3}-\\frac{2\\ln (u+1)}{3}=\\ln x+C,"

where C is some constant.

From here



"\\frac{u}{(u+1)^2}=Cx^3."

Thus



"\\frac{z}{(z+x)^2}=Cx^2."

So we have answer



"y^2=Cx^2(y^2+x)^2."

Answer. "y^2=Cx^2(y^2+x)^2."

Need a fast expert's response?

Submit order

and get a quick answer at the best price

for any assignment or question with DETAILED EXPLANATIONS!

Comments

No comments. Be the first!

Leave a comment

LATEST TUTORIALS
New on Blog